Sustainable agricultural knowledge-based entrepreneurship literacy in agricultural SMEs: Triple bottom line investigation - Muhammad Hasan; Tuti Supatminingsih; Thamrin Tahir; Feliks Arfid Guampe; Andrian Dolfriandra Huruta; Carol Yirong Lu (Journal of Open Innovation: Technology, Market and Complexity)
The relationship between sustainable agriculture, entrepreneurship, and innovation is an increasingly important global issue because sustainable agriculture contributes to a country's economy. This study aims to explore entrepreneurial literacy based on sustainable agricultural knowledge in agricultural SMEs and explore the application of sustainable agricultural knowledge in carrying out agricultural SMEs entrepreneurial activities. This study uses a qualitative approach with a case study method using data collection techniques through in-depth interviews. Key informants and supporting informants for the study are urban agricultural actors who carry out SMEs entrepreneurial activities in the agricultural sector. The triangulation technique used in this study increases the validity of the findings. Through an investigation using TBL, this study successfully explored entrepreneurial literacy based on sustainable agricultural knowledge in agricultural SMEs and explored the application of sustainable agricultural knowledge in carrying out agricultural SMEs entrepreneurial activities. This study can help develop concepts related to entrepreneurial literacy based on sustainable agricultural knowledge, especially when viewed from the intellectual capital approach within the knowledge-based view (KBV) framework and the open innovation approach. This study also serves as a foundation for the government to improve entrepreneurship education programs and entrepreneurial literacy based on sustainable agricultural knowledge, which can encourage the implementation of sustainable entrepreneurship.